Reconstructing the Roles and Responsibilities of Directors and Business Actors in Online Transactions in Star Up Companies Based on Justice Values - Ambarita, Lenny Mutiara; Hulu, Fonaho (Faculty of Law, Universitas Pekalongan, 2024)
This research discusses the roles and responsibilities of directors and business actors in online transactions in start-up companies with a focus on the value of justice. Digital technology has changed the way business is conducted, but a key challenge is ensuring fairness in online transactions, including transparency, data security and consumer protection. Using a qualitative approach with case studies on digital start-ups in Indonesia, the research results show that directors play an important role in establishing fair strategic policies, while business actors must implement these policies with integrity. In conclusion, this reconstruction of roles and responsibilities is important for creating a fair and sustainable business environment.